I'll be right there : a novel - Shin, Kyung-sook (Other Press, 2013)
While people vanish without a trace and others die senselessly, Jung Yoon matures into young adulthood as she loses her beloved mother, meets a once-in-a-lifetime mentor professor, forms and renews intimate friendships, and creates "forever" memories with her first love.